Effects of the single-lap joint on fatigue strength of metals with different surface coatings: a numerical simulation - Baykara, Celalettin; Teke, Ibrahim T.; Ertas, Ahmet H. (EDP Sciences, 2023)
Due to their low cost and ease of use, adhesives are frequently used in the industry. Selecting adherents and adhesives is essential when thinking about a construction that uses them. A fatigue study is therefore required to determine the best adherents and adhesives. In this situation, a prediction model must be incorporated into the process. In this study, Single-lap joint (SLJ) was chosen. Specimens with uncoated, primed, and cataphoresis-treated surfaces on DC01 steel sheet surfaces have been taken into account. A numerical solution was produced to obtain the fatigue life of the structures. Results indicate that the produced approach can provide an accurate estimate of fatigue resistance of different bonding methods including adhesive joints with various coating and adhesive thicknesses combined with adhesive techniques. © The Authors, published by EDP Sciences. This is an open access article distributed under the terms of the Creative Commons Attribution License 4.0 (https://creativecommons.org/licenses/by/4.0/).
2023 International Scientific Siberian Transport Forum, TransSiberia 2023 -- 2023-05-16 through 2023-05-19 -- Novosibirsk -- 190756